The Developmental Imperative and Counsellor Education - Van Hesteren, Frank (Canadian Journal of Counselling and Psychotherapy, 2011)
Following a brief account of the state of knowledge with regard to developmental approaches to counselling, it is argued that the developmental training imperative implicit in the counselling literature should be taken seriously. It is suggested that this might be done through more concentrated efforts to articulate the specifics of counsellor education along developmental lines. A constructive-developmental theoretical framework well suited to developmental counsellor training is presented and the manner of its incorporation into two core theory classes in a counsellor education program is described. Finally, an account is provided of how a training effort employing the constructive-developmental framework was experienced by participants, including the writer.